2017
DOI: 10.1016/j.cogdev.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind and school achievement: The mediating role of social competence

Abstract: Recent findings have highlighted the importance of children's social understandingspecifically their reasoning about beliefs and emotionsfor school achievement. However, little is known about the processes that may account for such a relationship. In this longitudinal study we examined the role of children's social competence (as indexed by peer relationships and social skills), using a multi-informant and multi-indicator approach. We followed 73 children during the transition to primary school, gathering data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 118 publications
0
35
0
1
Order By: Relevance
“…Early social cognition, for example, as the ability to understand other people's points of view and feelings, predicts children's subsequent school achievement and this pathway is mediated by children's level of social competence. 32 Implicit memory is also essential in learning and robust to cognitive disturbances. Research has shown preserved implicit memory in elderly and children with mental retardation.…”
Section: Discussionmentioning
confidence: 99%
“…Early social cognition, for example, as the ability to understand other people's points of view and feelings, predicts children's subsequent school achievement and this pathway is mediated by children's level of social competence. 32 Implicit memory is also essential in learning and robust to cognitive disturbances. Research has shown preserved implicit memory in elderly and children with mental retardation.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that, in a school‐based programme, those responses can be improved with young people who have difficulties in these areas. I work with a group of researchers from my collaborating department at the University of Pavia in Italy (Bianco, Lecce and Banerjee, ; Lecce, Caputi, Pagnin, et al., ). We do cross‐cultural work on social understanding that can be demonstrated to improve through conversation‐based intervention.…”
Section: Section 5: Personal Social and Emotional Learning: Accountmentioning
confidence: 99%
“…This result, therefore, empirically supports the practical value of inclusive classrooms and their importance for this population's development. Learning in inclusive classrooms as well as developing ToM is certainly important not only for children's present, but also for their future functioning and well-being (Fink, Begeer, Peterson, Slaughter, & de Rosnay, 2015;Kuhnert, Begeer, Fink, & de Rosnay, 2017;Lecce, Caputi, Pagnin, & Banerjee, 2017;O'Toole, Monks, & Tsermentseli, 2017).…”
Section: Con Clus Ionsmentioning
confidence: 99%